Separatism and Regionalism in Modern Europe - Kostov, Chris (Logos Verlag Berlin, 2020)
The end of the Cold War opened a Pandora's box of regionalism and separatism across Europe, and today they once again pose a significant threat to the territorial and political integrity of the traditional nation-states. Yet, the existence of various subnational groups is inevitable in democratic states. The scope of separatism and regionalism in Europe is quite wide. It includes de facto states, such as Kosovo, Transnistria, and North Cyprus; strong separatist movements aimed at achieving independence, like Catalonia, Basque Country, Scotland, Flanders, and Faroe Islands; strong movements aimed at achieving a more regional autonomy, for example, Lombardy and Veneto; and weaker regional movements, which could potentially escalate in the future, such as Transylvania in Romania or Vojvodina in Serbia. This edited volume tackles all the above-mentioned regional moments and even includes Greenland as a bonus. It brings together seventeen prominent scholars from a wide range of European and North American academic institutions who compiled ten chapters to shed light on the revival of regionalism and separatism via a thorough evaluation and analysis of some of the most important current separatist and regionalist/autonomist movements across modern Europe. Chris Kostov is an Adjunct Professor in the School of International Relations at IE University Madrid, Spain. He earned his PhD in History and Canadian Studies from the University of Ottawa, Canada. His main academic interests include Balkan and modern European nationalism and Communist repressions in Cold War Eastern Europe.